Airbnb and Rental Markets: Evidence from Berlin - Tomaso Duso; Claus Michelsen; Maximilian Schäfer; Kevin Ducbao Tran (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We exploit two policy interventions in Berlin, Germany, to causally identify the impact of Airbnb on rental markets. While the first intervention significantly reduced the number of high-availability Airbnb listings bookable for most of the year, the second intervention led to the exit of mostly occasional, low-availability listings. We find that the reduction in Airbnb supply has a much larger impact on rents and long-term rental supply for the first reform. This is consistent with more professional Airbnb hosts substituting back to the long-term rental market. Accordingly, we estimate that one additional nearby high-availability Airbnb listing crowds out 0.6 long-term rentals and, consequently, increases the asked square-meter rent by 1.8 percent on average. This marginal effect tends to be smaller in districts with a higher Airbnb density. However, these district experienced a larger slowdown in rent increases following the reform due to larger reductions in Airbnb supply.
Keywords: R21; R31; R52; Z30; 330; rents; housing market; short-term rental regulation; sharing economy; Airbnb